2014
DOI: 10.1080/19440049.2014.886340
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the migration of 15 photo-initiators from cardboard packaging into Tenax®using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS)

Abstract: Photo-initiators are widely used to cure ink on packaging materials used in food applications such as plastic films or cartonboards. In migration studies, food simulants are very often used to simulate food, like Tenax(®), which is the simulant for dry foodstuffs. In this paper a fast and reliable confirmation method for the determination of the following photo-initiators in Tenax(®) is described: benzophenone (BP), 4,4'-bis(diethylamino)benzophenone (DEAB), 2-chloro-9H-thioxanthen-9-one (CTX), 1-chloro-4-prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
(39 reference statements)
3
6
0
Order By: Relevance
“…However, a higher migration potential of photo-initiators towards rice was indicated in a rice matrix (Table 2). These results are of great consistency with the market survey performed in 2014 where significant amounts of photo-initiators were only found in several rice samples (Van Den Houwe et al, 2014).…”
Section: Evaluation Performance Tenax ® Filmsupporting
confidence: 89%
See 1 more Smart Citation
“…However, a higher migration potential of photo-initiators towards rice was indicated in a rice matrix (Table 2). These results are of great consistency with the market survey performed in 2014 where significant amounts of photo-initiators were only found in several rice samples (Van Den Houwe et al, 2014).…”
Section: Evaluation Performance Tenax ® Filmsupporting
confidence: 89%
“…The contaminants were selected based on a literature search on contaminants in paper and board. It was found that photo-initiators and phthalates are one of the most common groups of compounds present in paper and board food packaging (Aurela et al 1999;Jakubowska et al, 2014;Jung et al, 2013;Summerfield et al 2001;Van Den Houwe et al, 2014). Hence, two phthalates (BBP and DBP) and six photo-initiators (BP, DMPA, EDB, ITX, MBP and PBZ) were selected.…”
Section: Selection Of Contaminantsmentioning
confidence: 99%
“…The migration of 15 PIs into Tenax® was determined by UPLC‐MS/MS, from real paperboard packaged of dry food, collected in the Belgian market. Different PIs were found present, but the results for none of these samples exceeded the SML values 9 …”
Section: Introductionmentioning
confidence: 77%
“…In 2014, the migration of 15 photo‐initiators was evaluated by Van Den Houwe et al A multi‐method based on UPLC‐MS/MS was developed and applied to 15 real cardboard samples used for dry foodstuffs such as pasta, rice, cereals and bread crumbs …”
Section: Analytical Methodologymentioning
confidence: 99%